Housing ownership, incomes, and inequality in China: 2002 - 2007 - Hiroshi Sato; Terry Sicular; Ximing Yue (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Einkommensverteilung; Soziale Ungleichheit; Grundbesitz; Immobilien; China